Visual dysfunction and work invalidity in patients with diabetes and hypertension - Krstović Spremo, Vesna; Kekuš, Divna (PONS - medicinski časopis, 2023)
Diabetes mellitus and arterial hypertension are chronic, mass non-communicable diseases that are global health problems with characteristics of epidemiology and consecutive eye complications are the common reason for visual handicap and disability in the work productive population.Objective: The primary aim was to analyze the frequency of visual dysfunction, and behavioral habits in diabetic and hypertensive patients and the second aim was to analyze the occurrence of work disability in patients with these diseases.Methods:  The investigation is a cross-sectional study made in two Health Centers in the City of Eastern Sarajevo in a period of July 2018 to July 2019 (12 months). A randomized sample of 192 patients with diabetes and 100 hypertensive patients. For this purpose is created a special questionnaire, and statistic analysis is made by SPSS (IBM, Chicago version 19). Statistical significance was investigated with χ 2 test.Results: Diabetic patients significantly have more visual disturbances than hypertensive patients according to subjective assessment (χ2= 14.21, p< 0.001). Worsening of visual acuity is presented more in diabetic than in hypertensive patients (χ2 = 16.17, p < 0.001). There is no significant difference in behavioral habits between diabetic and hypertensive patients for smoking (χ2 =1.778, p=0.411) and alcohol consumption.( χ2 = 2.158, p = 0.142). Patients with diabetes are more frequent in the status of work disability than those with hypertension  (χ2 = 13,46, p < 0,001).Conclusion: Mass non-communicable diseases are a common cause of visual dysfunction and diabetes mellitus is the main reason for visual disability in the adult population from the region of Eastern Sarajevo. Behavioral habits like smoking and alcohol consumption have a serious impact on  the prognosis of those patients.
Keywords: diabetes; hypertension; visual disturbance